Enhanced wound healing promotion by immune response-free monkey autologous iPSCs and exosomes vs. their allogeneic counterparts - Lu, Meng (EBioMedicine, 2019)
BACKGROUND: Comparing non-inbred autologous and allogeneic induced pluripotent stem cells (iPSCs) and their secreted subcellular products among non-human primates is critical for choosing optimal iPSC products for human clinical trials. METHODS: iPSCs were induced from skin fibroblastic cells of adult male rhesus macaques belonging to four unrelated consanguineous families. Teratoma generativity, host immune response, and skin wound healing promotion were evaluated subsequently. FINDINGS: All autologous, but no allogeneic, iPSCs formed teratomas, whereas all allogeneic, but no autologous, iPSCs caused lymphocyte infiltration. Macrophages were not detectable in any wound. iPSCs expressed significantly more MAMU A and E of the major histocompatibility complex (MHC) class I but not more other MHC genetic alleles than parental fibroblastic cells. All topically disseminated autologous and allogeneic iPSCs, and their exosomes accelerated skin wound healing, as demonstrated by wound closure, epithelial coverage, collagen deposition, and angiogenesis. Allogeneic iPSCs and their exosomes were less effective and viable than their autologous counterparts. Some iPSCs differentiated into new endothelial cells and all iPSCs lost their pluripotency in 14 days. Exosomes increased cell viability of injured epidermal, endothelial, and fibroblastic cells in vitro. Although exosomes contained some mRNAs of pluripotent factors, they did not impart pluripotency to host cells. INTERPRETATION: Although all of the autologous and allogeneic iPSCs and exosomes accelerated wound healing, allogeneic iPSC exosomes were the preferred choice for “off-the shelf” iPSC products, owing to their mass-production, with no concern of teratoma formation. FUND: National Natural Science Foundation of China and National Key R&D Program of China.